Risk estimation of aviation transport system operation - Ширшов, В. Г. (Proceedings of National Aviation University (archive), 1999)
Considered are the methodical problems of risk estimation of aviation transport system (ATS) when accident factors which may cause failures of the component of ATS are revealed. Proposed is the necessity of systematic analysis of ATS components affecting the work of the aircraft, also proposed is a mathematical model which takes into account interaction of main components: aircraft, the crew, environment